Matter of competency-based approach - Oleg A. Donskikh (Высшее образование в России, 2022)
In the article it is shown that the orientation towards competences, which forms the basis of higher professional education reforming through the introduction of the new standards, rests on the mixture of two fundamentally different approaches. This results in the extremely poor quality standards and matrixes of correspondences, and does not lead to any achievement except the formation of methodic “foam”.